ISOLASI DAN SELEKSI JAMUR DAN BAKTERI ENDOFIT DARI TANAMAN MIMBA, BELUNTAS DAN GANDARUSA SEBAGAI PENGHASIL FUNGISTATIK DAN BAKTERIOSTATIK SCABIES - Rikka W. Sir; Arnold Ch. Tabun; Devi Y. Moenek (Partner, 2010)
Isolation and Selection of Endophytic Fungi and Bacteria from Mimba, Beluntas and Gandarusa used for Fungi Static and Bacteria Static Scabies. This research aim to get endophytic microbes from mimba, beluntas and gandarusa to produced bacteria static and fungi static to heal sufferer animal scabies. Microbes isolated from three kinds of plants was classified based on colony and cells shape. This research placed in Biotechnology Laboratory from June-November 2008 using Completely Randomized Design. There were three treatments of plant types and 3 repeats for each isolate. The result that there were two kinds of endophytic bacteria from mimba, one kind of endophytic fungi from beluntas and one kind of endophytic bacteria from gandarusa. Endophytic bacteria isolated from mimba leaf (MDB2) had a best potential to be fungi static for scabies.Keywords: isolation, selection, fungi static, bacteria static, scabies, mimba, gandarusa, beluntas.